Efficacy of diode laser irradiation during dental bleaching in preventing enamel damage caused by bleaching - Zahra Azarbayjani; Tahereh Sadat Jafarzadeh Kashi; Yasaman Erfan; Nasim Chiniforush; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2018)
Background: Evidence on the protecting effect of laser on bleached enamel is scarce and controversial. Therefore, we aimed to test for the first time whether different wavelengths of diode laser (810 and 980 nm) can prevent enamel surface corrosion. We also tested for the first time whether such therapeutic effects of laser are limited to specific "laser-activated" bleaching gels or both conventional and laser-activated gels. Materials and Methods: In this qualitative experimental study, ten intact human teeth were randomly assigned to five Groups. They were sectioned into twenty buccal/lingual pieces. The groups were: (1) laser-activated gel + 810 nm laser, (2) laser-activated gel + 980 nm laser, (3) conventional gel + 810 nm laser, (4) conventional gel + 980 nm laser, (5) conventional gel only, and (6) laser-activated gel - no irradiation. Buccal sections in each group were subjected to bleaching (according to the stated protocols), and later subjected to field-emission scanning electron microscopy (SEM) and X-ray diffraction (XRD). The lingual pieces were used as "before-treatment" negative controls for XRD. Results: XRD showed an increase in the mineral phase and crystallinity of the enamel in all bleaching groups. This was stronger in the laser-irradiated groups with conventional bleaching agent. SEM showed a complete etched surface in the positive control groups (i.e., bleached using conventional agent). However, all four laser groups had almost intact surfaces. Conclusion: This study showed the positive effect of diode laser irradiation at 810 nm or 980 nm wavelengths on the prevention of bleaching damage, irrespective of the activation mechanism of the bleaching gel in use.